The relationship of regional abdominal adiposity and adiposity‐related factors with cognitive functioning among middle‐aged individuals at high Alzheimer's dementia risk. Issue 10 (31st December 2021) - Boccara, Ethel; Golan, Sapir; Ravona‐Springer, Ramit; Inbar, Yael; Yore, Iscka; Heymann, Anthony; Beeri, Michal Schnaider
Abstract: Background: Obesity in midlife has been consistently associated with late‐life cognitive decline and Alzheimer's dementia (AD). Obesity is typically assessed by body mass index (BMI) rather than specific anatomical location of stored excess fat. These fat depots can affect the secretion of adipose‐related factors that in turn may affect AD risk. In this study we examined whether regional abdominal adiposity and adiposity‐related secreted factors are related to cognition in middle‐aged adults at high AD risk due to a parental history of AD. Method: Participants were from The Israel Registry for Alzheimer's Prevention (IRAP) study following middle‐aged offspring of Late‐Onset AD patients (N=390). To date, 46 participants who have complete cognitive assessment (summarized as global cognition and four cognitive domains—episodic memory, executive functions, language and working memory) have also been scanned for hepatic and pancreatic adiposity, and abdominal adipose tissue (AAT) via magnetic resonance imaging (MRI). Adiposity‐related factors primarily secreted by the liver (PAI‐1), visceral fat (TNF‐α), and the pancreas (PYY) were quantified by MILLIPLEX® MAP for 26 participants. Linear regressions examined the association of regional fat and adiposity‐related factors with cognition adjusting for age, sex, education, and BMI. Result: Participants (52% women) averaged 51.5 (SD=5.5) years of age, 17.3 (SD=2.1) years of education. Higher AAT was associated with lower global cognition (r=‐0.347, p=0.024), executive function (r=‐0.471, p=0.024) and approached significance for language (r=‐0.301, p=0.053). Higher hepatic fat was associated with lower executive functions (r=‐0.334, p=0.031) and the association of higher pancreatic fat with poorer executive function approached significance (r=‐0.273, p=0.081). All three adipose‐related secreted factors were associated with lower executive functions (PAI1 (r=‐0.635, p=0.003), TNF‐α (r=‐0.478, p=0.033) and PYY (r=‐0.420, p=0.065)) but not with global cognition or other cognitive domains. Conclusion: Higher regional abdominal adiposity and related secreted factors were associated with poorer cognitive functions, especially executive functions, already in midlife, in asymptomatic individuals enriched for AD risk, and regardless of global body fat measured by BMI. By AAIC 2021, we anticipate 100 IRAP participants will be assessed for regional abdominal adiposity and adipose‐related factors. Targeting regional adiposity is expected to prevent or delay cognitive decline, and ultimately AD.